2014
DOI: 10.1097/iae.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of White and Dark Without Pressure Fundus Lesions

Abstract: Both white and dark without pressure lesions are associated with changes in outer retinal reflectivity on optical coherence tomography, which occur in opposite directions compared with the surrounding unaffected areas. In the face of normal visual field testing to date, the clinical significance of this finding remains uncertain. Recognition of the optical coherence tomography appearance will help clinicians avoid unnecessary workup of these patients for outer retinal dystrophy or degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 4 publications
5
36
0
Order By: Relevance
“…Fawzi et al 4 reported that the OCT characteristics of these 'dark without pressure' lesions consist of hyporeflectivity of photoreceptor zones, consistent with the OCT findings in our cases. As in our study, no vitreoretinal alterations were found on OCT, although the authors acknowledge the possibility that the changes may have been precipitated by vitreous traction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Fawzi et al 4 reported that the OCT characteristics of these 'dark without pressure' lesions consist of hyporeflectivity of photoreceptor zones, consistent with the OCT findings in our cases. As in our study, no vitreoretinal alterations were found on OCT, although the authors acknowledge the possibility that the changes may have been precipitated by vitreous traction.…”
Section: Discussionsupporting
confidence: 80%
“…In a series of 10 patients with 'white' or 'dark without pressure,' 6 of 7 patients with 'dark without pressure' were of pigmented race, whereas 2 of 3 patients with 'white without pressure' were Caucasian. 4 In our series, all patients were of pigmented race with hyperpigmented fundi, and this may have led to the appearance of 'dark without pressure' rather than 'white without pressure. ' In Cases 4-6, longer follow-up revealed a decrease in the shadow sign, which may be related to the theoretical breakdown of the vitreous with age reducing the Elevated appearing pigmented lesion with a well-demarcated shadow anteriorly, with disappearance after 3 years Figure 1 Ultra wide-field color fundus photograph of a 41-yearold Hispanic female demonstrating a well-demarcated 'shadow sign' anterior to a CHRPE lesion (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…1 Subsequent cases described as "dark without pressure" revealed EZ hyporeflectivity, whereas patients with "white without pressure" demonstrated hyperreflectivity of these zones; in these patients, the vitreoretinal interface appeared normal, and the authors postulated that these lesions represented a spectrum of varying intrinsic photoreceptor reflectivity. 2 In a cohort of nine children with achromatopsia, six had EZ disruption, with one having a complete hyporeflective EZ subfoveally. 3 Our patient did not have EZ band hyporeflectivity in the macula, noted normal color perception and contrast sensitivity, and he was able to see 10/10 color plates correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Ellipsoid zone hyporeflectivity has been described in asymptomatic patients and in patients with severe visual dysfunction from cone-rod dystrophies or posttreatment with ocriplasmin. [1][2][3][4] Advances in ophthalmic imaging modalities have allowed for greater characterization of these lesions, leading to new insight into the underlying pathophysiology.…”
mentioning
confidence: 99%
“…NIR imaging showed distinct morphological features and reflectance between infants and the other three groups as well as an obvious tendency that the reflectance of choroidal vascular components accumulated with age. Due to the long wavelength, NIR can penetrate through melanin and lipofuscin [14] and, therefore, enable visualization of the choroid and may also detect pathological changes despite the presence of hemorrhages or cataracts [15]. In addition, NIR minimizes pre-stimulation of the retina, avoiding the effects of absorption changes caused by photopigment bleaching.…”
Section: Discussionmentioning
confidence: 99%